The relationship between Alertness entrepreneurial and strategic supremacy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is goings to discuss the practical aspects of investigating the Alertness entrepreneurial development of an enterprise in the face of challenges of a new industrial society. The necessity of a systematic assessment of the Alertness entrepreneurial of strategic supremacy with a sectoral and territorial community as an important information resource of a digital technological platform and an object of regional industrial policy management has been substantiated.